The effect of adding Proprioceptive Neuromuscular Facilitation (PNF) training on quadriceps and hamstrings muscle strength in cerebral palsy athletes - Al Hazmy, Abdullah; Subadi, Imam; Andriati, Andriati; Indriani, Diah; Setianing, Retno; Saputra Perdana, Suryo; Ferdianto, Rima (Retos (Madrid), 2025)
Introduction: Athletes with CP were more prone to limb injuries. Stretching had long been considered beneficial for improving muscle performance and reducing the risk of injury. Proprioceptive Neuromuscular Facilitation was a technique used to enhance muscle elasticity and increase peak torque and muscle strength. Objective: To analyze the effect of adding Proprioceptive Neuromuscular Facilitation exercises on quadriceps and hamstring muscle strength in cerebral palsy athletes. Methodology: The study was conducted at the NPC Indonesia Training Center. The subjects consisted of 24 athletes diagnosed with cerebral palsy, aged 18-40 years, who underwent intervention three times per week for four weeks on both limbs. The subjects were divided into two groups: 12 individuals in the treatment group received a resistance training program with additional Proprioceptive Neuromuscular Facilitation exercises, and 12 in the control group underwent resistance training only. Results: There was a significant increase in muscle strength in the treatment group for the dominant quadriceps (p=0.043), non-dominant quadriceps (p=0.001), dominant hamstring (p=0.002), and non-dominant hamstring (p=0.008). In the control group, significant increases were observed in the dominant hamstring (p=0.024) and non-dominant hamstring (p=0.013), but not in the dominant quadriceps (p=0.530) or non-dominant quadriceps (p=0.420). Compared to the control group, a significant difference was found in non-dominant quadriceps strength (p=0.020), but no differences were observed in dominant quadriceps strength (p=0.396) or hamstring strength (p=0.271, p=0.204). Conclusions: The addition of Proprioceptive Neuromuscular Facilitation exercises significantly increased quadriceps and hamstring strength in cerebral palsy athletes compared to those without it.